Cortisol, testosterone, and free testosterone in athletes performing a marathon at 4,000 m altitude - Marinelli, M.; Roi, G. S.; Giacometti, M.; Bonini, P.; Banfi, G. (Hormone Research, 1994)
Cortisol, testosterone, free testosterone and the ratio between free testosterone and cortisol (FTCR) were monitored in six athletes participating in a marathon starting at 3,860 and finishing at 3,400 m, having reached the top at 5,100 m altitude. Blood was drawn at sea level before the departure for the mountain area, after a week of acclimatization, immediately after the marathon and after a 24-hour recovery period from the run. Cortisol increased after acclimatization and especially after the marathon; it decreased to normal values after recovery. Testosterone decreased after acclimatization, especially after the run; it presented a partial recovery 24 h after the race. Free testosterone did not decrease after acclimatization and presented partial recovery. FTCR could also be useful for monitoring fitness, overtraining and overstrain in strenuous and ultraendurance exercise.